Self-Regulated Learning for Learning to Learn in Higher Education - Rosales-Marquez , Cinthia; Silva-Aguilar, Agueda; Miranda-Vargas , Victor; Salas-Sanchez, Rosa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The challenging changes have impacted learning, creating the need for new ways of learning, such as self-regulated learning. This approach facilitates the development of competencies by promoting metacognition and learning to learn. The objective of this study was to analyze research on the topic to extract its contributions. A qualitative systematic review was conducted, searching for articles in Scopus, WOS, and PubMed in both English and Spanish, and 30 documents were selected. It was evidenced that self-regulated learning contributes comprehensively and significantly to the achievement of competencies, analyzed through its cognitive, metacognitive, affective-emotional, relational-social, and ethical dimensions.